The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1016/j.compenvurbsys.2009.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for evaluating automated map generalization in commercial software

Abstract: This paper presents a methodology developed for a study to evaluate the state of the art of automated map generalization in commercial software without applying any customization. The objectives of this study are to learn more about generic and specific requirements for automated map generalization, to show possibilities and limitations of commercial generalization software, and to identify areas for further research. The methodology had to consider all types of heterogeneity to guarantee independent testing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 78 publications
(102 citation statements)
references
References 10 publications
1
96
0
Order By: Relevance
“…align-along-road) which integrates the relationship to surrounding roads. The typology proposed in this paper is regarded to be generic as all of the pattern types are confirmed by studying the maps (of the Netherlands, France, and Spain) in the EuroSDR generalization study (Stoter et al, 2009a), and maps of China, examples are shown in Figure 2. Other higher-level or global pattern can be seen as spatial combination of these low-level patterns and the integration of these patterns with other information such as semantics.…”
Section: Identifying and Characterizing The Typologymentioning
confidence: 99%
“…align-along-road) which integrates the relationship to surrounding roads. The typology proposed in this paper is regarded to be generic as all of the pattern types are confirmed by studying the maps (of the Netherlands, France, and Spain) in the EuroSDR generalization study (Stoter et al, 2009a), and maps of China, examples are shown in Figure 2. Other higher-level or global pattern can be seen as spatial combination of these low-level patterns and the integration of these patterns with other information such as semantics.…”
Section: Identifying and Characterizing The Typologymentioning
confidence: 99%
“…In the EuroSDR project, cartographic experts of four national mapping agencies (NMAs) were called to evaluate the results of the automation generalisation process according to certain constraints (Stoter et al, 2009). The objective of this project consists to illustrate the state of the art of automated generalisation in practice, exchange of knowledge between research community, NMAs and software vendor and to contribute to the development of constraint specification.…”
Section: State Of Art For On-the-fly Web Map Generalisationmentioning
confidence: 99%
“…Stoter et al [32] comprehensively studied map specifications for automated map generalization (i.e., selection and simplified representation of details appropriate to the scale and/or purpose of a map [17]). In their results, the authors listed graphical measures for both single objects and groups of objects.…”
Section: Readability Measures In Dataset Specifications and Cartograpmentioning
confidence: 99%